Experimental chemitry: A laboratory course - Manus B Monroe (Star, 1991)
The book assigns experiments covering such topics as electrochemistry and organic chemistry. Detailed and specific directions guide through the experiments. This book also offers descriptive inorganic and organic chemistry, instrumentation, student research projects and concentration cells - topics that are infrequently found but presentied here in an appropriate manner as a foundation for future classes